Two-stage efficiency evaluation of production and pollution control in Chinese iron and steel enterprises. (1st November 2017) - Chen, Lili; He, Feng; Zhang, Qingzhi; Jiang, Wei; Wang, Jianjian
Abstract: Previous studies on the efficiency of traditional iron and steel enterprises have primarily investigated the efficiency of the production phase and have often overlooked the efficiency of pollution controls included in the overall process of iron and steel enterprises. In this study, we investigated the efficiency of the production chain in China and the efficiency of pollution control. In addition, a two-stage model of production and pollution control was established considering undesirable outputs, and the overall efficiency of the iron and steel enterprises were analyzed. From the results, the efficiency of iron and steel enterprises and the efficiency of pollution control were determined to be generally low. Furthermore, pollution control processes were less efficient than production processes, indicating a strong potential for improvement of the efficiency of iron and steel enterprises. Finally, the impact of environmental regulation on the efficiency of iron and steel enterprises formed an "inverted N-type" relationship. Highlights: A two-stage model of iron and steel production and pollution control is proposed. Overall, pollution control tends to be overlooked in iron and steel enterprises. A general trade-off between pollution control and production observed. Room for much improvements in iron and steel enterprises regarding both factors. Investment in environmental protection and more efforts in research are required.